Preparation method and application of blue-light CsPbBr3 perovskite quantum dots

By introducing 1-ethyl-3-methylimidazolium hexafluorophosphate onto the surface of blue CsPbBr3 quantum dots, defects are passivated and Auger recombination is suppressed, thus solving the problems of spectral drift and surface defects of blue CsPbBr3 quantum dots under external influences and realizing a high-efficiency, long-life blue light-emitting diode.

CN120966475AActive Publication Date: 2025-11-18UNIV OF ELECTRONICS SCI & TECH OF CHINA

Patent Information

Application Number
CN202511492150.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2025-11-18
Estimated Expiration
2045-10-20

AI Technical Summary

Technical Problem

Existing blue CsPbBr3 quantum dots are susceptible to halide ion migration under external influences, leading to irreversible spectral shifts, reduced color purity, and surface defects affecting Auger recombination, which reduces optical performance and the stability of the light-emitting diode.

Method used

A heterogeneous ligand exchange strategy was employed to introduce 1-ethyl-3-methylimidazolium hexafluorophosphate onto the quantum dot surface, which passivated surface defects and suppressed Auger recombination. By forming strong bonds with lead dangling bonds and cesium sites on the quantum dot surface, the coupling effect between quantum dots was weakened.

Benefits of technology

The optical performance and stability of quantum dots have been improved, the photoluminescence quantum yield has been increased from 78% to 92%, the blue light-emitting diodes maintain high external quantum efficiency under high brightness, and the operating life has been significantly extended, reaching the industry-leading level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120966475A_ABST
    Figure CN120966475A_ABST
Patent Text Reader

Abstract

The invention aims to provide a preparation method and application of a blue-light CsPbBr3 perovskite quantum dot, and belongs to the technical field of quantum dot preparation. According to the method, 1-ethyl-3-methylimidazolium hexafluorophosphate molecules are introduced to the surfaces of the quantum dots by using a heterogeneous ligand exchange strategy, and passivation of surface defects of the quantum dots and inhibition of Auger recombination are realized at the same time, so that the optical performance and stability of the quantum dots are improved, and the photoluminescence quantum yield is increased from 78% to 92%; according to a blue light emitting diode prepared based on the CsPbBr3 quantum dot, the maximum external quantum efficiency of 20.02% is achieved under the brightness of 6441 cd / m < 2 >, and the external quantum efficiency of nearly 19% is still achieved under the high brightness of nearly 10000 cd / m < 2 >; under the initial brightness of 106 cd / m < 2 >, the running half-life period of about 700 minutes is obtained; the preparation of the blue-light perovskite quantum dot light-emitting diode with high external quantum efficiency, high brightness, long service life and low efficiency roll-off is realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of quantum dot preparation, and relates to preparation of blue light perovskite quantum dots, in particular to a preparation method and application of blue light CsPbBr3 perovskite quantum dots. BACKGROUND

[0002] Information display technology is an important measure of the level of national information development. Active light-emitting display technology based on light-emitting diodes has the advantages of high brightness, bright colors, environmental protection and energy saving, and has become the mainstream development route of information display technology. As one of the three primary colors in display technology, the performance of blue light-emitting diodes directly determines the quality of display. As a new type of luminescent material, cesium lead halide perovskite (CsPbX3, X = Cl, Br, I) quantum dots have great potential in the field of new generation high-definition display due to their narrow emission bandwidth, high defect tolerance, wide color gamut and simple synthesis process, and are considered to be a strong competitor of rare earth materials and organic luminescent materials.

[0003] Currently, there are mainly two methods for preparing blue light-emitting cesium lead halide perovskite quantum dots, namely using mixed halogen component engineering and strong quantum confinement effect. Mixed halogen component engineering is still the most commonly used method for synthesizing blue light perovskite quantum dots, but still faces many bottlenecks, for example: under the action of external factors such as electric field and light field, halogen ions in blue light mixed halogen perovskite (CsPbBr 3-x Cl x ) quantum dots are very easy to migrate, resulting in irreversible movement of the spectrum of quantum dots and devices, thereby reducing color purity. In contrast, blue light CsPbBr3 quantum dots synthesized by using strong quantum confinement effect well solve the problem of poor spectral stability of CsPbBr 3-x Cl x quantum dots. However, as the size of quantum dots decreases, its specific surface area will continue to increase, thereby exacerbating the influence of surface defects on blue light CsPbBr3 quantum dots and Auger recombination.

[0004] Therefore, developing a new method that can effectively passivate the surface defects of blue light CsPbBr3 quantum dots, stabilize the surface of quantum dots and inhibit Auger recombination is crucial for improving the optical properties, stability of blue light perovskite quantum dots and the performance of light-emitting diodes based thereon. SUMMARY

[0005] In view of the problems existing in the background art, the purpose of the present application is to provide a preparation method and application of blue light CsPbBr3 perovskite quantum dots. The present application introduces 1-ethyl-3-methyl imidazole hexafluorophosphate to the surface of quantum dots by using a heterogeneous ligand exchange strategy, while achieving the passivation of quantum dot surface defects and the inhibition of Auger recombination, thereby improving the optical performance and stability of the quantum dots, and realizing the preparation of blue light perovskite quantum dot light-emitting diodes with high external quantum efficiency, high brightness, long running life and low efficiency roll-off.

[0006] To achieve the above purpose, the technical scheme of the present application is as follows:

[0007] A preparation method of blue light CsPbBr3 perovskite quantum dots, comprising the following steps:

[0008] Step 1. Preparation of blue light CsPbBr3 quantum dot crude solution;

[0009] Step 2. The obtained blue light CsPbBr3 quantum dot crude solution and methyl acetate are sequentially added to a centrifugal tube, and then centrifugal treatment is carried out, the precipitate obtained by centrifugation is dispersed in a non-polar solvent, and methyl acetate is added again, centrifugation is carried out again, and then the obtained precipitate is dispersed in a non-polar solvent again to obtain a first quantum dot dispersion liquid;

[0010] Step 3. 1-ethyl-3-methyl imidazole hexafluorophosphate is added to a reaction container, and then the first quantum dot dispersion liquid is added, stirred and filtered to obtain a blue light CsPbBr3 perovskite quantum dot dispersion liquid.

[0011] Further, the ratio of the mass of 1-ethyl-3-methyl imidazole hexafluorophosphate to the volume of the first quantum dot dispersion liquid is 5-17 mg / mL.

[0012] Further, the specific process of preparing the blue light CsPbBr3 quantum dot crude solution in step 1 is as follows:

[0013] Step 1.1. Cesium carbonate and oleic acid are sequentially added to octadecene, stirred, and gradient heating is carried out under vacuum conditions, and then nitrogen replacement is carried out, the atmosphere of the reaction container is replaced with nitrogen to obtain a first precursor solution;

[0014] Step 1.2. Lead bromide, zinc bromide and octadecene are mixed, and then gradient heating is carried out under vacuum conditions, and then nitrogen replacement is carried out, and then oleic acid and oleylamine are added and stirred to obtain a second precursor solution;

[0015] Step 1.3. The temperature of the second precursor solution is set to 115-125 ℃, the first precursor solution is added to the second precursor solution under the nitrogen environment, and after a period of incubation, the solution is taken out, stirred and cooled to room temperature in an ice water bath to obtain a blue light CsPbBr3 quantum dot crude solution; wherein the volume ratio of the second precursor to the first precursor is 11-14.

[0016] Further, in step 1.1, the mass of cesium carbonate to the volume of octadecene is 8-12 mg / mL, and the volume of oleic acid to the volume of octadecene is 0.06-0.08; in step 1.2, the mass of lead bromide to the volume of octadecene is 13-15 mg / mL, the mass of zinc bromide to the volume of octadecene is 67-69 mg / mL, the volume of oleic acid to the volume of octadecene is 0.45-0.55, and the volume of oleylamine to the volume of octadecene is 0.45-0.55.

[0017] Further, in step 1.1, the gradient heating condition is 40 ℃, 60 ℃, and 100 ℃ in turn, and each temperature stage is kept for 10 minutes; in step 1.2, the gradient heating condition is 40 ℃, 60 ℃, 100 ℃, and 120 ℃ in turn, and each temperature stage is kept for 10 minutes.

[0018] Further, in step 2, the volume ratio of the first time adding methyl acetate to the volume of the quantum dot crude solution is 3.4-4.0, the volume of the first time adding the non-polar solvent is 1 mL, the volume of the second time adding methyl acetate is 2-3 mL, and the volume of the second time adding the non-polar solvent is 0.4-0.6 mL; the non-polar solvent is one or more of n-octane, n-hexane, and toluene.

[0019] The application also provides the application of the blue light CsPbBr3 perovskite quantum dots prepared by the above preparation method in a blue light emitting diode.

[0020] Further, the preparation process of the blue light emitting diode is as follows:

[0021] S1. Preparing a poly(3,4-ethylenedioxythiophene) polystyrene sulfonate / poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) film on an indium tin oxide-glass substrate;

[0022] S2. Spinning a blue light CsPbBr3 perovskite quantum dot dispersion on the surface of the poly(3,4-ethylenedioxythiophene) polystyrene sulfonate / poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) film to obtain a perovskite quantum dot film;

[0023] S3. Covering a patterned mask plate on the surface of the perovskite quantum dot film, and then performing vacuum thermal evaporation, and sequentially evaporating 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene, lithium fluoride and an electrode on the surface of the perovskite quantum dot film at an evaporation rate of 0.2-0.4 Å / s, so that the required perovskite quantum dot-based blue light-emitting diode is prepared.

[0024] Further, in S1, the specific preparation process of the poly(3,4-ethylenedioxythiophene) polystyrene sulfonate / poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) film is as follows:

[0025] The indium tin oxide-glass substrate is cleaned, dried by using a nitrogen gun and subjected to ultraviolet-ozone treatment;

[0026] The poly(3,4-ethylenedioxythiophene) polystyrene sulfonate aqueous solution is spin-coated on the surface of the indium tin oxide-glass substrate subjected to the ultraviolet-ozone treatment, and annealing treatment is performed at a temperature of 145-155 ℃ for 8-12 minutes, and after the treatment is completed, the temperature is cooled to room temperature;

[0027] The poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) chlorobenzene solution (4-6 mg / mL) is spin-coated on the surface of the poly(3,4-ethylenedioxythiophene) polystyrene sulfonate film, and annealing treatment is performed at a temperature of 145-155 ℃ for 13-17 minutes, and after the treatment is completed, the temperature is cooled to room temperature, so that the poly(3,4-ethylenedioxythiophene) polystyrene sulfonate / poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) film is prepared on the indium tin oxide-glass substrate.

[0028] Further, in S3, the thickness of the 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene layer is 45-55 nm, the thickness of the lithium fluoride layer is 0.9-1.1 nm, and the thickness of the electrode is 100 nm.

[0029] The mechanism of the present application is as follows:

[0030] The present application uses a heterogeneous ligand exchange strategy to introduce 1-ethyl-3-methylimidazolium hexafluorophosphate molecules to replace part of the original oleic acid and oleylamine on the surface of the quantum dots to stabilize the surface of the quantum dots. 1-ethyl-3-methylimidazolium hexafluorophosphate can partially ionize into 1-ethyl-3-methylimidazolium cations and hexafluorophosphate ions in a non-polar solvent, and the hexafluorophosphate ions can strongly bond with the lead dangling bonds and cesium sites of the quantum dots, and at the same time, the large steric hindrance thereof weakens the coupling effect between the quantum dots; the 1-ethyl-3-methylimidazolium cations will bond with the bromine dangling bonds of the quantum dots, passivating the surface defects of the quantum dots, which has a significant inhibitory effect on Auger recombination, and together improves the optical performance and stability of the quantum dots;

[0031] To sum up, due to the adoption of the above technical scheme, the beneficial effects of the present application are:

[0032] 1、The photoluminescence spectrum of the CsPbBr3 quantum dots prepared by the method is 475 nm, belonging to the blue light band; the quantum dots have excellent optical performance and stability, the photoluminescence quantum yield is improved from 78% to 92%, and the preparation method is simple and easy to operate.

[0033] 2、The blue light emitting diode prepared based on the CsPbBr3 quantum dots has a maximum external quantum efficiency (20.02%) under a luminance of 6441 cd / m2, and still has an external quantum efficiency of nearly 19% under a high luminance of nearly 10000 cd / m2, which belongs to the industry leading level; under an initial luminance of 106 cd / m2, a running half-life of nearly 700 minutes (the running time corresponding to the luminance of the light emitting diode being attenuated to half of the initial value) is obtained, which is 125 times of the blue quantum dot based light emitting diode without optimization. 2 2 BRIEF DESCRIPTION OF DRAWINGS

[0034] Figure 1 is the adsorption energy of hexafluorophosphate ions and 1-ethyl-3-methyl imidazole cations on the surface of CsPbBr3 quantum dots.

[0035] Figure 2 is the ultraviolet-visible absorption spectrum and photoluminescence spectrum of the CsPbBr3 quantum dots synthesized in Example 1 and the comparative example; Among them, (a) is the photoluminescence spectrum of the CsPbBr3 quantum dots synthesized in the comparative example, (b) is the photoluminescence spectrum of the CsPbBr3 quantum dots synthesized in Example 1, and (c) is the ultraviolet-visible absorption spectrum of the CsPbBr3 quantum dots synthesized in Example 1 and the comparative example.

[0036] Figure 3 is the scanning- transmission electron microscope image and size distribution diagram of the CsPbBr3 quantum dots synthesized in Example 1 and the comparative example; Among them, (a) is the scanning- transmission electron microscope image of the CsPbBr3 quantum dots synthesized in the comparative example, (b) is the scanning- transmission electron microscope image of the CsPbBr3 quantum dots synthesized in Example 1, (c) is the size distribution diagram of the CsPbBr3 quantum dots synthesized in the comparative example, and (d) is the size distribution diagram of the CsPbBr3 quantum dots synthesized in Example 1.

[0037] Figure 4 is the photoluminescence quantum yield of the CsPbBr3 quantum dots synthesized in Example 1 and the comparative example.

[0038] ​​Figure 5 Time-resolved femtosecond transient absorption spectra of CsPbBr3 quantum dots synthesized in Example 1 and Comparative Example; Wherein, (a) is the femtosecond transient absorption spectrum of the Comparative Example, (b) is the femtosecond transient absorption spectrum of Example 1.

[0039] Figure 6 Current density-luminance-voltage curves of blue light-emitting diodes based on CsPbBr3 quantum dots synthesized in Example 1 and Comparative Example.

[0040] Figure 7 External quantum efficiency-luminance curves of blue light-emitting diodes based on CsPbBr3 quantum dots synthesized in Example 1 and Comparative Example.

[0041] Figure 8 Operating lifetimes of blue light-emitting diodes based on CsPbBr3 quantum dots synthesized in Example 1 and Comparative Example. DETAILED DESCRIPTION

[0042] In order to make the objects, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with reference to the embodiments and drawings.

[0043] Example 1

[0044] A preparation method of blue light CsPbBr3 perovskite quantum dots, comprising the following steps:

[0045] Step 1. Preparation of blue light CsPbBr3 quantum dot crude solution, the specific process is as follows:

[0046] Step 1.1. 10 mL of octadecene, 0.7 mL of oleic acid and 100 mg of cesium carbonate were added into a three-necked flask, which was transferred to a heating jacket, and then stirred at a speed of 250 revolutions per minute, and gradient heating was carried out in a vacuum environment, and the step temperatures were 40 ℃, 60 ℃, 100 ℃ respectively, and the time intervals were all 10 minutes; then the gas environment in the three-necked flask was replaced by nitrogen using a Hileck line, and a first precursor solution was obtained;

[0047] Step 1.2. 10 mL of octadecene, 140 mg of lead bromide and 680 mg of zinc bromide were added into another three-necked flask, which was transferred to a heating jacket, and then stirred at a speed of 400 revolutions per minute, and gradient heating was carried out in a vacuum environment, and the step temperatures were 40 ℃, 60 ℃, 100 ℃, 120 ℃ respectively, and the time intervals were all 10 minutes; then the gas environment in the three-necked flask was replaced by nitrogen using a Hileck line, and then 5 mL of oleic acid and 5 mL of oleylamine were sequentially injected into the three-necked flask, and the stirring speed was increased to 700 revolutions per minute, and then the solution in the three-necked flask became clear and transparent, and a second precursor solution was obtained;

[0048] Step 1.3. Take 1.6 mL of the first precursor solution and inject it into the second precursor solution at a temperature of 120 ℃, and after 5 seconds of incubation, take the flask out and place it in an ice water bath to cool to room temperature, obtaining a blue light CsPbBr3 quantum dot crude solution;

[0049] Step 2. In a centrifuge tube, add 80 mL of methyl acetate as an anti-solvent to the obtained blue light CsPbBr3 quantum dot crude solution, centrifuge at a speed of 10,000 rpm for 1 minute, discard the supernatant, add 1 mL of n-octane to the precipitate, shake, and then continue to add 2.5 mL of methyl acetate as an anti-solvent, centrifuge at a speed of 12,000 rpm for 1 minute, discard the supernatant, and disperse the precipitate with 0.5 mL of n-octane to obtain a first quantum dot dispersion;

[0050] Step 3. Transfer the first quantum dot dispersion to a vial containing 5 mg of 1-ethyl-3-methylimidazolium hexafluorophosphate, and place the vial on a magnetic stirrer at a speed of 300 rpm for 30 seconds. Then filter the ligand-exchanged quantum dot dispersion using a microfiltration head to obtain a blue light CsPbBr3 perovskite quantum dot dispersion.

[0051] The CsPbBr3 quantum dots synthesized in this example were used to prepare a blue light emitting diode, and the specific process was as follows:

[0052] S1. Clean the indium tin oxide-glass substrate: first wash carefully with glass cleaning solution, then ultrasonically clean the substrate in ultrapure water and anhydrous ethanol for 30 minutes each, after which dry the substrate with nitrogen and place it in a UV-ozone environment for 25 minutes;

[0053] S2. Prepare a poly(3,4-ethylenedioxythiophene) polystyrene sulfonate film on the cleaned indium tin oxide-glass substrate: use a spin coater to spin coat the purchased poly(3,4-ethylenedioxythiophene) polystyrene sulfonate aqueous solution evenly on the surface of the indium tin oxide-glass substrate, with a spin speed of 4,000 rpm and a spin time of 40 seconds. After spin coating, place the substrate on a hot plate at 150 ℃ for annealing, with an annealing time of 10 minutes. After completion, transfer the substrate to a culture dish and cool it to room temperature naturally.

[0054] S3. Preparing poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) film on the surface of poly(3,4-ethylenedioxythiophene) polystyrene sulfonate film by spin coating: transferring the substrate into a nitrogen glove box, using a spin coater to uniformly spin coat the purchased poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) chlorobenzene solution (5 mg / mL) on the surface of the poly(3,4-ethylenedioxythiophene) polystyrene sulfonate film at a rotation speed of 4000 rpm for 45 seconds, then transferring the substrate to a hot stage at 150°C for annealing treatment, the annealing time is 15 minutes, after completion, transferring it to a culture dish and naturally cooling to room temperature to obtain a poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) film;

[0055] S4. Uniformly spin coating blue light CsPbBr3 perovskite quantum dot dispersion on the surface of the poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) film to prepare a blue light CsPbBr3 quantum dot film, the spin coating parameters are as follows: rotation speed of 2000 rpm and time of 40 seconds;

[0056] S5. Covering the perovskite quantum dot film with a patterned mask plate, and sequentially depositing 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, lithium fluoride and aluminum electrodes on the surface thereof by vacuum thermal evaporation; the pressure in the vacuum thermal evaporation chamber is less than 5x10 -4 Pa, the evaporation rate is 0.3 Å / s, the thickness of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene is 50 nm, the thickness of lithium fluoride is 1 nm, and the thickness of the aluminum electrode is 100 nm, thereby obtaining a blue light-emitting diode based on CsPbBr3 quantum dots.

[0057] Example 2

[0058] A blue light-emitting diode based on CsPbBr3 quantum dots was prepared according to the procedure of Example 1, except that the ratio of the mass of cesium carbonate to the volume of octadecene in step 1.1 was adjusted to 8 mg / mL, the ratio of the volume of oleic acid to the volume of octadecene was adjusted to 0.06, the ratio of the mass of lead bromide to the volume of octadecene in step 1.2 was adjusted to 13 mg / mL, the ratio of the mass of zinc bromide to the volume of octadecene was adjusted to 67 mg / mL, the ratio of the volume of oleic acid to the volume of octadecene was adjusted to 0.45, and the ratio of the volume of oleylamine to the volume of octadecene was adjusted to 0.45; the temperature of the second precursor solution in step 1.3 was adjusted to 115°C;

[0059] The ratio of the volume of the first methyl acetate addition to the volume of the crude quantum dot solution in Step 2 was adjusted to 3.4, and the volume of the second methyl acetate addition was adjusted to 2 mL; the ratio of the mass of 1-ethyl-3-methylimidazolium hexafluorophosphate to the volume of the first quantum dot dispersion in Step 3 was adjusted to 5 mg / mL; and the non-polar solvent added both times was adjusted to n-hexane.

[0060] The annealing temperature in S2 and S3 was adjusted to 145 ℃; the annealing time in S2 was adjusted to 8 minutes, and the annealing time in S3 was adjusted to 13 minutes; the concentration of the poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) chlorobenzene solution in S3 was adjusted to 4 mg / mL; in S4, the evaporation rate was adjusted to 0.2 Å / s, the thickness of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene was adjusted to 45 nm, and the thickness of lithium fluoride was 0.9 nm; and the other steps were unchanged.

[0061] Example 3

[0062] A blue light-emitting diode based on CsPbBr3 quantum dots was prepared according to the steps of Example 1, except that the ratio of the mass of cesium carbonate to the volume of octadecene in Step 1.1 was adjusted to 12 mg / mL, the ratio of the volume of oleic acid to the volume of octadecene was adjusted to 0.08, the ratio of the mass of lead bromide to the volume of octadecene in Step 1.2 was adjusted to 15 mg / mL, the ratio of the mass of zinc bromide to the volume of octadecene was adjusted to 69 mg / mL, the ratio of the volume of oleic acid to the volume of octadecene was adjusted to 0.55, and the ratio of the volume of oleylamine to the volume of octadecene was adjusted to 0.55; the temperature of the second precursor solution in Step 1.3 was adjusted to 125 ℃.

[0063] The ratio of the volume of the first methyl acetate addition to the volume of the crude quantum dot solution in Step 2 was adjusted to 4.0, and the volume of the second methyl acetate addition was adjusted to 3 mL; the ratio of the mass of 1-ethyl-3-methylimidazolium hexafluorophosphate to the volume of the first quantum dot dispersion in Step 3 was adjusted to 17 mg / mL; and the non-polar solvent added both times was adjusted to toluene.

[0064] The annealing temperature in S2 and S3 was adjusted to 155 ℃; the annealing time in S2 was adjusted to 12 minutes, and the annealing time in S3 was adjusted to 17 minutes; the concentration of the poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) chlorobenzene solution in S3 was adjusted to 6 mg / mL; in S4, the evaporation rate was adjusted to 0.4 Å / s, the thickness of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene was adjusted to 55 nm, and the thickness of lithium fluoride was 1.1 nm; and the other steps were unchanged.

[0065] Comparative Example

[0066] Blue light CsPbBr3 quantum dots and blue light emitting diodes were prepared according to the steps of Example 1, except that step 3 was not performed.

[0067] Figure 1 The adsorption energy of hexafluorophosphate ions and 1-ethyl-3-methyl imidazole cations on the surface of the quantum dots. The negatively charged hexafluorophosphate ions tend to bond with the positively charged lead dangling bonds and cesium sites, and the positively charged 1-ethyl-3-methyl imidazole cations tend to bond with the negatively charged bromine dangling bonds. According to the first-principles calculation, the adsorption energy of the two ions in the 1-ethyl-3-methyl imidazole hexafluorophosphate on the surface of the quantum dots is negative, indicating that both of them have a bonding effect with the surface of the quantum dots. Among them, the absolute value of the adsorption energy of the hexafluorophosphate ion on the surface of the quantum dots is significantly greater than that of the 1-ethyl-3-methyl imidazole cation (|-279.8 kcal / mol| > |-16.8 kcal / mol|), indicating that the bonding force between the hexafluorophosphate ion and the lead dangling bonds and cesium sites of the quantum dots is stronger, which is a strong bonding effect.

[0068] Figure 2 The ultraviolet-visible absorption spectrum and photoluminescence spectrum of the CsPbBr3 quantum dots synthesized in Example 1 and the comparative example, wherein Figure (a) is the photoluminescence spectrum of the CsPbBr3 quantum dots synthesized in the comparative example, Figure (b) is the photoluminescence spectrum of the CsPbBr3 quantum dots synthesized in Example 1, and Figure (c) is the ultraviolet-visible absorption spectrum of the CsPbBr3 quantum dots synthesized in Example 1 and the comparative example. As can be seen from Figures (a) and (b), compared with the CsPbBr3 quantum dots synthesized in the comparative example, the photoluminescence peak of the CsPbBr3 quantum dots prepared in Example 1 is slightly blue-shifted by 1 nm, which is 475 nm, still belonging to the blue light band, and the half-width is narrowed by 1 nm, which is 26 nm. At the same time, it can be seen from Figure (c) that the CsPbBr3 quantum dots before and after passivation with 1-ethyl-3-methyl imidazole hexafluorophosphate all have a clear exciton absorption peak, indicating that the 1-ethyl-3-methyl imidazole hexafluorophosphate molecules introduced in the present application do not change the strong quantum confinement characteristics of the quantum dots.

[0069] Figure 3Scanning-Transmission Electron Microscope images and size distribution plots of CsPbBr3 quantum dots synthesized in Example 1 and Comparative Example, wherein Figure (a) is a Scanning-Transmission Electron Microscope image of CsPbBr3 quantum dots synthesized in Comparative Example, Figure (b) is a Scanning-Transmission Electron Microscope image of CsPbBr3 quantum dots synthesized in Example 1, Figure (c) is a size distribution plot of CsPbBr3 quantum dots synthesized in Comparative Example, and Figure (d) is a size distribution plot of CsPbBr3 quantum dots synthesized in Example 1. Comparing Figure (a) and (b), it can be seen that the distance between the CsPbBr3 quantum dots prepared in Example 1 is increased, which weakens the coupling effect, suppresses the fluorescence resonance energy transfer between the quantum dots, and improves the luminescence performance of the quantum dots; at the same time, the CsPbBr3 quantum dots prepared in Example 1 have a higher arrangement order (the arrangement order of Example 1 is 0.94, and the arrangement order of Comparative Example is 0.86); in addition, there are almost no lead nanocrystals on the surface of the CsPbBr3 quantum dots prepared in Example 1 due to high-energy electron irradiation (the brighter area on the surface of the quantum dots in the figure), which means that the quantum dots synthesized in Example 1 have a more stable surface. Comparing Figure (c) and (d), it can be seen that the average size of the quantum dots synthesized in Example 1 is 4.0 nm, which is slightly smaller than that of the quantum dots synthesized in Comparative Example (the average size is 4.2 nm), which indicates that the introduction of 1-ethyl-3-methylimidazolium hexafluorophosphate does not significantly affect the size of the quantum dots, i.e., does not weaken the confinement effect of the quantum dots.

[0070] Figure 4 Photoluminescence quantum yield of CsPbBr3 quantum dots synthesized in Example 1 and Comparative Example. As can be seen from the figure, after introducing 1-ethyl-3-methylimidazolium hexafluorophosphate to the surface of the quantum dots, the photoluminescence quantum yield of the CsPbBr3 quantum dots synthesized in Example 1 is increased from 78% to 92% compared with Comparative Example, which indicates that the introduction of 1-ethyl-3-methylimidazolium hexafluorophosphate molecules reduces the trap state density on the surface of the quantum dots, thereby suppressing the non-radiative recombination of carriers and increasing the radiative recombination rate of carriers.

[0071] Figure 5 Time-dependent femtosecond transient absorption spectra of CsPbBr3 quantum dots synthesized in Example 1 and Comparative Example, wherein Figure (a) is Comparative Example, and Figure (b) is Example 1. As can be seen from the figure, the replacement of the original long-chain ligand molecules on the surface of the quantum dots by 1-ethyl-3-methylimidazolium hexafluorophosphate significantly reduces the decay of the absorption spectrum of the quantum dots under high excitation intensity (26 µJ / cm 2 ), i.e., effectively suppresses the Auger recombination of CsPbBr3 quantum dots under high carrier density.

[0072] Figure 6The current density-luminance-voltage curve of the blue light emitting diode based on the CsPbBr3 quantum dots synthesized in Example 1 and the comparative example shows that the blue light emitting diode prepared in Example 1 has a lower turn-on voltage (2.6 V) and a higher luminance (13389 cd / m 2 ) compared with the comparative example, which indicates that the 1-ethyl-3-methylimidazolium hexafluorophosphate improves the charge injection inside the light emitting diode, makes the charge injection more balanced, and stabilizes the surface of the quantum dots, so that the device can achieve higher luminance.

[0073] Figure 7 The external quantum efficiency-luminance curve of the blue light emitting diode based on the CsPbBr3 quantum dots synthesized in Example 1 and the comparative example shows that the quantum dot-based light emitting diode prepared in Example 1 achieves a higher external quantum efficiency (20.02%) at a luminance of 6441 cd / m 2 , and still has an external quantum efficiency of nearly 19% at a high luminance of nearly 10000 cd / m 2 . Some tin-based and bismuth-based perovskite materials developed in recent years are far behind cesium-lead halide perovskite in photoelectric performance and cannot be applied to the preparation of high-performance light emitting diodes. The results of the present application represent an important step towards the blue perovskite light emitting diode for high-definition display, and set a world record for the current blue perovskite light emitting diode.

[0074] Figure 8 The operation half-life of the blue light emitting diode based on the CsPbBr3 quantum dots synthesized in Example 1 and the comparative example shows that the light emitting diode prepared in Example 1 achieves an operation half-life of nearly 700 minutes at an initial luminance of 106 cd / m 2 , which is 125 times that of the light emitting diode prepared based on the comparative example, and is a world record for the blue perovskite light emitting diode prepared by vacuum thermal evaporation process.

[0075] The above is only a specific embodiment of the present application, and any feature disclosed in the specification can be replaced by other equivalent or similar purpose alternative features unless specifically stated; all features disclosed, or steps in all methods or processes, except mutually exclusive features and / or steps, can be combined in any way.

Claims

1. A method for preparing blue CsPbBr3 perovskite quantum dots, characterized in that, Includes the following steps: Step 1. Prepare a crude solution of blue-light-emitting CsPbBr3 quantum dots; Step 2. Add the obtained blue CsPbBr3 quantum dot crude solution and methyl acetate to a centrifuge tube in sequence, then centrifuge. Disperse the precipitate obtained by centrifugation in a non-polar solvent, add methyl acetate again, centrifuge again, and then redisperse the precipitate in a non-polar solvent to obtain the first quantum dot dispersion. Step 3. Add 1-ethyl-3-methylimidazolium hexafluorophosphate to the reaction vessel, then add the first quantum dot dispersion, stir, and filter to obtain a blue CsPbBr3 perovskite quantum dot dispersion.

2. The method for preparing blue CsPbBr3 perovskite quantum dots as described in claim 1, characterized in that, The mass ratio of 1-ethyl-3-methylimidazolium hexafluorophosphate to the volume of the first quantum dot dispersion is 5–17 mg / mL.

3. The method for preparing blue CsPbBr3 perovskite quantum dots as described in claim 1, characterized in that, The specific process for preparing the crude solution of blue CsPbBr3 quantum dots in step 1 is as follows: Step 1.

1. Cesium carbonate and oleic acid are added to octadecene in sequence, stirred, and heated under vacuum conditions with a gradient. Then, nitrogen is used to replace the atmosphere of the reaction vessel with nitrogen to obtain the first precursor solution. Step 1.

2. After mixing lead bromide, zinc bromide and octadecene, the mixture is heated under vacuum with a gradient, then replaced with nitrogen, and then oleic acid and oleylamine are added and stirred to obtain the second precursor solution. Step 1.

3. Set the temperature of the second precursor solution to 115~125 ℃. Under nitrogen atmosphere, add the first precursor solution to the second precursor solution. After keeping it at this temperature for a period of time, take it out and place it in an ice-water bath to stir and cool to room temperature to obtain a crude solution of blue CsPbBr3 quantum dots. The volume ratio of the second precursor to the first precursor is 11~14.

4. The method for preparing blue CsPbBr3 perovskite quantum dots as described in claim 3, characterized in that, In step 1.1, the mass ratio of cesium carbonate to octadecene is 8-12 mg / mL, and the volume ratio of oleic acid to octadecene is 0.06-0.08; in step 1.2, the mass ratio of lead bromide to octadecene is 13-15 mg / mL, the mass ratio of zinc bromide to octadecene is 67-69 mg / mL, the volume ratio of oleic acid to octadecene is 0.45-0.55, and the volume ratio of oleylamine to octadecene is 0.45-0.

55.

5. The method for preparing blue CsPbBr3 perovskite quantum dots as described in claim 3, characterized in that, In step 1.1, the gradient heating conditions are 40 ℃, 60 ℃, and 100 ℃ in sequence, with each temperature stage held for 10 minutes; in step 1.2, the gradient heating conditions are 40 ℃, 60 ℃, 100 ℃, and 120 ℃ in sequence, with each temperature stage held for 10 minutes.

6. The method for preparing blue CsPbBr3 perovskite quantum dots as described in claim 1, characterized in that, In step 2, the volume ratio of methyl acetate to the crude quantum dot solution added for the first time is 3.4 to 4.0, the volume of the non-polar solvent added for the first time is 1 mL, the volume of methyl acetate added for the second time is 2 to 3 mL, and the volume of the non-polar solvent added for the second time is 0.4 to 0.6 mL; the non-polar solvent is one or more of n-octane, n-hexane, and toluene.

7. The present invention also provides the application of blue CsPbBr3 perovskite quantum dots obtained by the preparation method of blue CsPbBr3 perovskite quantum dots as described in any one of claims 1-6 in blue light-emitting diodes.

8. The application of blue CsPbBr3 perovskite quantum dots as described in claim 7 in blue light-emitting diodes, characterized in that, The fabrication process of the blue light-emitting diode is as follows: S1. Preparation of poly(3,4-ethylenedioxythiophene)polystyrene sulfonate / poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) thin films on indium tin oxide-glass substrates; S2. Blue CsPbBr3 perovskite quantum dot dispersion was spin-coated onto the surface of a poly(3,4-ethylenedioxythiophene)polystyrene sulfonate / poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) film to obtain a perovskite quantum dot film; S3. A patterned mask is coated on the surface of a perovskite quantum dot film, and then vacuum thermal evaporation is performed to sequentially deposit 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, lithium fluoride, and electrodes on the surface of the perovskite quantum dot film at a evaporation rate of 0.2~0.4 Å / s, thereby obtaining the desired blue light-emitting diode based on perovskite quantum dots.

9. The application of blue CsPbBr3 perovskite quantum dots as described in claim 8 in blue light-emitting diodes, characterized in that, In S1, the specific preparation process of the poly(3,4-ethylenedioxythiophene)polystyrene sulfonate / poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) film is as follows: Clean the indium tin oxide-glass substrate, dry it with a nitrogen gun, and then treat the substrate with ultraviolet-ozone. An aqueous solution of poly(3,4-ethylenedioxythiophene) polystyrene sulfonate was spin-coated onto the surface of an indium tin oxide-glass substrate that had undergone UV-ozone treatment, and then annealed at 145-155 °C for 8-12 minutes, followed by cooling to room temperature. Then, a poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)chlorobenzene solution is spin-coated onto the surface of the poly(3,4-ethylenedioxythiophene)polystyrene sulfonate film, and annealed at 145~155 ℃ for 13~17 minutes. After annealing, the film is cooled to room temperature, and a poly(3,4-ethylenedioxythiophene)polystyrene sulfonate / poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) film can be prepared on an indium tin oxide-glass substrate.

10. The application of blue CsPbBr3 perovskite quantum dots as described in claim 8 in blue light-emitting diodes, characterized in that, In S3, the thickness of the 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene layer is 45~55 nm, the thickness of the lithium fluoride layer is 0.9~1.1 nm, and the thickness of the electrode is 100 nm.

Citation Information

Patent Citations

  • Perovskite light-emitting diode with QD-3D-QD light-emitting layer and preparation method of perovskite light-emitting diode

    CN108767125A

  • Preparation method of novel magnetic fluorescent bifunctional nano material

    CN111849478A

  • Perovskite light-emitting diode

    CN113725378A

  • Perovskite quantum dot photoresist as well as preparation method and application method thereof

    CN117631449A

  • Method for synthesizing blue light CsPbBr3 quantum dots with assistance of ionic liquid at room temperature and product prepared by method

    CN118206987A

Cited By

  • Preparation method of red light perovskite quantum dot with core-shell structure

    CN120966473A